Business Cycle in the US and five ASEAN countries: are they related? - Ong, Hway-Boon; Puah, Chin Hong; Muzafar Shah, Habibullah (UP School of Economics (UPSE), 2004)
Given the inter-country linkages arising from technological advances in communication and transportation, this paper examines the interdependent relationships between the output of the world's largest economy, the U.S, and those of five other ASEAN countries, namely Indonesia, Malaysia, Philippines, Singapore and Thailand. Based on result of the augmented VAR of the Granger non-causality test, the paper finds a weak interdependence between the U.S and the five ASEAN countries, but a strong interdependence among the ASEAN countries. The empirical findings also revealed bi-directional causality among ASEAN countries especially Malaysia and Singapore. As such, every ASEAN country has to consider the economic developments and policies of other ASEAN countries as their decisions could affect one another.